The Phenomenon of Mudik as an Annual Social Practice: An Analysis of the Dynamics of Solidarity and Social Relations in Indonesian Society - Sefiani Dwi Azmi (PT. AVID MEDIA INDONESIA, 2026)
The phenomenon of mudik (Eid homecoming) in Indonesia represents a significant socio-cultural practice that reflects the dynamics of social solidarity, kinship, and collective identity. In the context of modernization and digital transformation, mudik serves as a social mechanism that reconnects individuals with their familial and communal roots while counterbalancing urban individualism. This study aims to analyze mudik as a form of social solidarity based on traditions and social relations in Indonesian society. This research employs a qualitative approach with a descriptive-analytical design, combining library research and limited field observation. Data were collected through document analysis, in-depth interviews, and observation, and analyzed using data reduction, data display, and conclusion verification with triangulation to ensure validity. The findings reveal that mudik strengthens familial, communal, and religious solidarity through direct social interaction, collective rituals, and cultural practices. It also functions as a hybrid space integrating traditional and modern forms of social relations. However, challenges such as digital dependency, commercialization, and the temporary nature of mudik limit its long-term impact on social cohesion. In conclusion, mudik plays a vital role in reinforcing social solidarity in Indonesia, but its sustainability requires broader cultural and structural support to maintain long-term social cohesion in a rapidly changing society